KEKUASAAN DALAM PEMIKIRAN IBNU KHALDUN - Muhammad Redy Alvan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
There are different things from the view of Ibn Khaldun the focus of political science itself. In line with Aristotle that human beings are involved in politics (zoon politicon), that the main object of study is the man himself and his relationship with the universe. Simply put, Ibn Khaldun puts man as great as a regulator of the life on earth.Keywords : Thinking, Power